Electrolyte with high and low temperature performance under high voltage and lithium ion battery

By using a combined additive of boron trifluoride complex lithium salt of pyrosulfate, cyclic sulfonate ester compounds and lithium oxalate salt in the lithium ion battery electrolyte, and adjusting the content ratio, the problem of lithium ion battery under high voltage is solved. The problem of deterioration of electrochemical performance and safety performance is achieved, and excellent performance under high and low temperature conditions is achieved.

CN119340475AActive Publication Date: 2025-01-21ZHEJIANG LANTIAN ENVIRONMENTAL PROTECTION HI TECH CO LTD +1

Patent Information

Application Number
CN202310883889.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21
Estimated Expiration
2043-07-19

AI Technical Summary

Technical Problem

At high voltage, the electrochemical and safety performance of lithium-ion batteries will be deteriorated, and existing additives have shortcomings in high-temperature performance and low-temperature performance, especially in high-voltage environments of high-nickel systems.

Method used

Use an electrolyte containing at least three additives: pyrosulfate boron trifluoride complex lithium salt, cyclic sulfonate ester compounds and oxalate lithium salt. By adjusting the content ratio of these additives, a synergistic effect is formed to reduce battery impedance and improve battery resistance. High and low temperature performance.

Benefits of technology

It effectively reduces battery impedance under high voltage, inhibits gas production in high-temperature storage, improves the high-temperature and low-temperature performance of the battery, and ensures the stability and performance of the battery in high-nickel system and high-voltage environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340475A_ABST
    Figure CN119340475A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte with high and low temperature performance under high voltage and a lithium ion battery. The electrolyte comprises a first additive and a second additive, the first additive at least comprises pyrosulfate boron trifluoride composite lithium salt with a structure shown in a formula (I-1): # imgabs0 #, a cyclic sulfonate compound serving as a second additive and oxalate lithium salt serving as a third additive, and the first additive, the second additive and the third additive respectively account for a%, b% and c% of the total mass of the electrolyte, the following relational expressions are met: 0.2 < = b + c < = 4; 0.2 < = b / c < = 10; 0.07 < = (b + c) / a < = 20. The electrolyte is used for the lithium ion secondary battery, the battery impedance can be reduced under the high voltage larger than or equal to 4.3 V, meanwhile, high-temperature storage gas production of the battery is restrained, and the high-temperature performance and the low-temperature performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium ion battery electrolyte, and in particular to an electrolyte containing at least three additives, namely, pyrosulfate boron trifluoride composite lithium salt, cyclic sulfonate compound and oxalate lithium salt, and a lithium ion battery containing the electrolyte. Background Art

[0002] Lithium-ion secondary batteries have the advantages of high energy density, long cycle life, and environmental friendliness, and are widely used in the fields of power, digital, etc. As the energy density requirements for lithium batteries become higher and higher, the 4.3V operating voltage of commercial lithium-ion batteries is difficult to meet the requirements, but the increase in battery operating voltage often accelerates the oxidative decomposition of conventional electrolytes, resulting in poor electrochemical and safety performance of the battery.

[0003] At present, sulfonate additives such as 1,3-propane sultone (PS) and 1,3-propylene sultone (PST) are recognized as good high-temperature additives for use under high voltage. They form a protective film under high voltage, which is insoluble in organic solvents and can allow lithium ions to freely deintercalate in the electrode without allowing solvent molecules to pass through, effectively preventing further reaction between the organic components of the electrolyte and the electrode and thus damaging the electrode. However, sulfonate additives increase battery impedance and have poor low-temperature performance, which poses serious difficulties when used in power-type batteries with high low-temperature performance requirements.

[0004] Another example is LiDFOP, which contains lithium oxalate salts, which have the effect of reducing impedance but often have poor high-temperature performance under high voltage. Although patent CN103943884A discloses that lithium oxalate salts as additives can improve the high-temperature and low-temperature performance of electrolytes, it does not explain that the lithium-ion battery produced therefrom can still maintain excellent high-temperature and low-temperature performance under high-voltage systems.

[0005] Pyrosulfate boron trifluoride composite lithium salt is a new electrolyte additive developed by Zhejiang Chemical Research Institute Co., Ltd. Its patent CN202211583064.X discloses that the additive can improve the battery's cycle performance, high-temperature storage performance and low-temperature performance. At the same time, patent CN202211583043.8 also discloses the use of pyrosulfate boron trifluoride composite lithium salt, vinyl sulfate and / or 1,3-propanesulfonic acid lactone in combination, or the further addition of vinylene carbonate in combination, so that lithium-ion batteries still have excellent cycle performance, high-temperature storage performance and the effect of inhibiting battery gas production in high energy density systems and high voltage environments, and can inhibit the impedance growth during the battery cycle and further improve low-temperature performance. However, in the high-voltage working environment of the high-nickel system, especially the positive electrode working voltage ≥4.3V, although lithium salt additives have the advantage of reducing impedance, they face the risk of insufficient high-temperature performance under high voltage in the high-nickel system.

[0006] Therefore, it is a very important research topic at present to continue in-depth research to develop more electrolyte formulas with good stability, low battery impedance at high voltage or even ultra-high voltage, and significant comprehensive performance such as high temperature performance, low temperature performance, and charge and discharge rate performance. Summary of the invention

[0007] In order to solve the above technical problems, the present invention further proposes an electrolyte comprising at least three additives: pyrosulfate boron trifluoride complex lithium salt, cyclic sulfonate compounds and oxalate lithium salt. The electrolyte is used in lithium-ion secondary batteries. At a high voltage of ≥4.3V, it can still effectively reduce the battery impedance, while inhibiting the gas production of the battery during high-temperature storage, thereby improving the high-temperature performance and low-temperature performance of the battery.

[0008] The objective of the present invention is achieved through the following technical solutions:

[0009] An electrolyte having both high and low temperature performance under high voltage, the electrolyte comprising: a main lithium salt, a non-aqueous solvent and an additive, specifically, the additive comprising:

[0010] The first additive comprises at least a pyrosulfate boron trifluoride composite lithium salt having a structure shown in the following formula (I-1):

[0011]

[0012] The second additive is selected from the cyclic sulfonate compounds represented by the following formula (IIA) and / or (IIB):

[0013]

[0014] Wherein, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 are independently selected from hydrogen, C1-C3 alkyl or halogen, m and n are independently selected from 1, 2 or 3, and in each repeating unit, R5, R6, R9, R 10 may be selected from the same or different substituents;

[0015] The third additive is a lithium oxalate salt having a structure shown in the following formula (III):

[0016]

[0017] In formula (III), R 11 , R 12 independently selected from C1-C3 alkyl, C1-C3 haloalkyl or halogen, R 13 is selected from a direct bond, a C1-C3 alkylene group or a halogenated C1-C3 alkylene group, M is selected from a boron atom or a phosphorus atom, and p is selected from 1 or 2;

[0018] The first additive, the second additive and the third additive account for a%, b% and c% of the total mass of the electrolyte respectively, and meet the following relationship:

[0019] 0.2≤b+c≤4;

[0020] 0.2≤b / c≤10;

[0021] 0.07≤(b+c) / a≤20.

[0022] Preferably, the addition amounts of the first additive, the second additive and the third additive satisfy the following relationship:

[0023] 1≤b+c≤2.5;

[0024] 0.5≤b / c≤7.5;

[0025] 1≤(b+c) / a≤12.5.

[0026] In the electrolyte of the present invention, by using the first additive, the second additive and the third additive together and adjusting the usage ratio of the three, the battery impedance can be significantly reduced, and the high temperature storage performance, high temperature cycle and low temperature performance can be improved. When the usage ratio of the three does not meet the above conditions, the lithium-ion battery cannot simultaneously reduce the battery impedance and improve the high temperature storage performance, high temperature cycle performance and low temperature performance.

[0027] Specifically, in the electrolyte of the present invention, the sum of the contents of the second additive and the third additive is between 0.2 and 4, preferably between 1 and 2.5. Once the sum of the contents of the two is too small (such as less than 0.2), the negative electrode film-forming effect is not significantly improved, and the high-temperature effect is not significantly improved; once the sum of the contents of the two is too large (such as greater than 4), the battery impedance will increase and the low-temperature performance will deteriorate.

[0028] In the electrolyte of the present invention, the ratio of the content of the second additive to that of the third additive is between 0.2 and 10, preferably between 0.5 and 7.5. Once the ratio of the content of the second additive to that of the third additive is too small (such as less than 0.2), the content of the third additive is excessive, the negative electrode film-forming effect is not significantly improved, and the high-temperature performance is deteriorated; once the ratio of the content of the second additive to that of the third additive is too large (such as greater than 10), the content of the second additive is excessive, the negative electrode film is thicker, the battery impedance will be increased, and the low-temperature performance will be deteriorated.

[0029] In the electrolyte of the present invention, the ratio of the sum of the contents of the second additive and the third additive to the first additive is between 0.07 and 20, preferably between 1 and 12.5. Once the ratio is too small (such as less than 0.07), the negative electrode film-forming effect is not significantly improved, and the high-temperature performance deteriorates; once the ratio is too large (such as greater than 20), the battery impedance will increase and the low-temperature performance will deteriorate.

[0030] After meeting the specific content ratio relationship between the first additive, the second additive and the third additive, the respective amounts of the first additive, the second additive and the third additive must still meet the following requirements, namely:

[0031] 0.2≤a≤3. If the amount of the first additive added is too low (such as less than 0.2), the negative electrode film-forming effect is poor, the battery impedance increases, and the low-temperature performance decreases; if the amount of the first additive added is too high (such as higher than 3), the high-temperature performance of the battery decreases.

[0032] 0.1≤b≤2.5. If the amount of the second additive added is too low (such as less than 0.1), the negative electrode film-forming effect is poor and the high-temperature performance of the battery is reduced; if the amount of the second additive added is too high (such as higher than 2.5), the battery impedance increases and the low-temperature performance is reduced.

[0033] 0.1≤c≤2.5. If the amount of the third additive added is too low (such as less than 0.1), the negative electrode film formation effect is poor, the battery impedance increases, and the low temperature performance decreases; if the amount of the third additive added is too high (such as higher than 2.5), the high temperature performance of the battery decreases.

[0034] During the preparation process of the first additive of the present invention, due to different preparation processes, in addition to the pyrosulfate boron trifluoride composite lithium salt of the structure shown in (I-1) above, it will also include at least one of the compounds shown in the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6):

[0035]

[0036]

[0037] The first additive contains at least 80 wt% of the pyrosulfate boron trifluoride complex lithium salt of the structure shown in formula (I-1). Preferably, the first additive contains 80-95 wt% of the pyrosulfate boron trifluoride complex lithium salt of the structure shown in formula (I-1), and the rest is at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6).

[0038] In the second additive of the present invention, preferably, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 are independently selected from hydrogen, methyl, ethyl or halogen, m and n are independently selected from 1 or 2, and in each repeating unit, R5, R6, R9, R 10 are selected from the same or different substituents.

[0039] Further preferably, the second additive is selected from at least one of the cyclic sulfonate compounds shown in the following structures:

[0040]

[0041]

[0042] In the third additive of the present invention, R 11 , R 12 are independently selected from halogen, R 13 is selected from a direct bond, a methylene group or a fluoromethylene group; more preferably, the third additive is selected from at least one of the lithium oxalate salts shown in the following structure:

[0043]

[0044] The pyrosulfate boron trifluoride composite lithium salt, cyclic sulfonate compounds and oxalate lithium salt of the present invention are used in the electrolyte at the same time, and the three can play a synergistic role, and none of them can be missing. Although the synergistic mechanism of the three has not yet been fully clarified, it is speculated through experimental conclusions that the three can inhibit the reaction intensity of cyclic sulfonate compounds at about 2.35V to 2.40V, inhibit the reaction consumption of non-aqueous solvents such as EC at about 2.65V to 2.75V, and control the content of the three to achieve the regulation of the reaction intensity at the negative electrode, so that an organic-inorganic multi-component composite SEI film rich in inorganic salt components such as Li2SO4, Li2SO3 and -SOB- cross-linked network organic components is formed at the negative electrode, which inhibits the performance degradation caused by the reaction of cyclic sulfonate compounds and / or oxalate lithium salts at the negative electrode, thereby reducing the battery impedance and improving the high-temperature storage performance, high-temperature cycle performance and low-temperature performance

[0045] Furthermore, the electrolyte of the present invention further comprises a fourth additive, which is vinylene carbonate, and the mass percentage of the fourth additive in the electrolyte is 0.1 to 5 wt %; preferably, the mass percentage of the vinylene carbonate in the electrolyte is 0.15 to 3.0 wt %.

[0046] As a film-forming additive, vinylene carbonate is added on the basis of the first additive, the second additive and the third additive. Vinylene carbonate reacts continuously during the cycle process to form a stable and dense polymer film on the electrode surface, thereby inhibiting the embedding of solvent molecules to destroy the electrode, thereby improving battery performance.

[0047] According to the application scenarios of different electrolytes and the requirements of battery electrochemical performance, a basic additive is further added to the electrolyte of the present invention, wherein the basic additive is selected from at least one of a sulfate compound, a fluorinated carbonate compound or a fluorinated lithium salt compound, and the amount thereof accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte;

[0048] The sulfate compound is selected from at least one of vinyl sulfate, pentaerythritol bicyclic sulfate, 4,4'-disulfate or 4-methyl-vinyl sulfate;

[0049] The fluorinated carbonate compound is selected from at least one of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylpropylene carbonate;

[0050] The fluorine-containing lithium salt compound is selected from at least one of lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium difluorobis(oxalate) phosphate, lithium difluorooxalate borate, lithium trioxalate phosphate or the lithium salt represented by the following formula (IV), and the fluorine-containing lithium salt compound is different from the main lithium salt:

[0051]

[0052] In formula (IV), y+z=4, y≥0 and z≥1, and y and z are positive integers.

[0053] In a specific embodiment, the basic additive is a combination of 0.2-1.0% by mass of lithium difluorophosphate, 0.2-1.0% by mass of lithium bis(fluorosulfonyl)imide and 0.2-0.8% by mass of ethylene fluorocarbonate, which can further optimize the positive and negative electrode-electrolyte interface film components and improve the low temperature discharge performance and rate charging performance of the battery.

[0054] In another specific embodiment, the basic additive is a combination of 0.2-3.0% by mass of lithium bis(fluorosulfonyl)imide and 0.1-1.0% by mass of fluoroethylene carbonate, which can also improve the low-temperature discharge performance and rate charging performance of the battery.

[0055] According to the electrolyte of the present invention, the main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium trioxalate phosphate or lithium difluorobis(oxalate) phosphate, and its molar concentration is 0.1-4.0 mol / L; preferably, the main lithium salt is selected from lithium hexafluorophosphate and / or lithium bis(fluorosulfonyl imide), and its concentration in the electrolyte is 0.5-1.5 mol / L.

[0056] The non-aqueous solvent is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, fluoroethylene carbonate, difluoroethylene carbonate, γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate, propyl propionate, cyclopentane, dimethyl sulfoxide, dimethyl sulfone, diethyl sulfone, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether or 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0057] In the actual application of electrolyte formulation, organic solvents are all complex multi-component systems. Among them, cyclic carbonates have a high dielectric constant and can better dissolve lithium salts to provide high conductivity; linear carbonates and carboxylates can effectively adjust the viscosity and liquid range of the electrolyte. By matching different types of solvents, an organic solvent system with more suitable comprehensive performance can be achieved.

[0058] Further preferably, the non-aqueous solvent of the present invention is selected from at least two of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, fluoroethylene carbonate, ethyl acetate, ethyl propionate, propyl acetate, cyclopentane, dimethyl sulfone or 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0059] The present invention also provides a lithium ion secondary battery, comprising a positive electrode, a negative electrode, a separator, and any one of the above-mentioned electrolytes.

[0060] In the lithium-ion secondary battery of the present invention, the active material of the positive electrode is selected from ternary nickel cobalt lithium manganese oxide, lithium cobalt oxide, lithium iron manganese phosphate, spinel lithium manganese oxide or lithium nickel manganese oxide, and the active material of the negative electrode is selected from graphite and / or silicon negative electrode materials. Preferably, the ternary nickel cobalt lithium manganese oxide is selected from NCM523 (LiNi 0.5 Co 0.2 Mn 0.3 O2), NCM622(LiNi 0.6 Co 0.2 Mn 0.2 O2), NCM712(LiNi 0.7 Co 0.1 Mn 0.2 O2), NCM811(LiNi 0.8 Co 0.1 Mn 0.1 O2) or NCM90505(LiNi 0.9 Co 0.05 Mn 0.05 More preferably, the ternary nickel cobalt lithium manganese oxide is selected from NCM622 (LiNi 0.6 Co 0.2 Mn 0.2 O2) or NCM712(LiNi 0.7 Co 0.1 Mn 0.2 O2).

[0061] The operating voltage of the lithium ion secondary battery of the present invention is ≥4.3V, preferably ≥4.4V, such as 4.4V, 4.48V, 4.52V, etc.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] The present invention uses a pyrosulfate boron trifluoride composite lithium salt, a cyclic sulfonate compound and an oxalate lithium salt in combination, and controls the three additives within a specific content ratio range to fully produce a synergistic effect, thereby obtaining a suitable film-forming potential, inhibiting the reaction intensity of the cyclic sulfonate compound at about 2.35V to 2.40V, inhibiting the reaction consumption of non-aqueous solvents such as EC at about 2.65V to 2.75V, and controlling the content of the three to control the reaction intensity at the negative electrode, forming a multi-component composite SEI film at the negative electrode, thereby reducing the battery impedance, improving the low-temperature performance, and improving the high-temperature storage performance and high-temperature cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0064] Attached Figure 1 The dQ / dV curves of Example 1, Comparative Example 5, Comparative Example 6 and Comparative Example 7 of the present invention are shown. DETAILED DESCRIPTION

[0065] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.

[0066] In the embodiments and comparative examples of the present invention, the types of the first additive include the following:

[0067] The first additive A1 is composed of 95 wt% of compound I-1 and 5 wt% of compound I-2;

[0068] The first additive A2 is composed of 90 wt% of compound I-1, 6 wt% of compound I-2 and 4 wt% of compound I-3;

[0069] The first additive A3 consists of 85 wt % of compound I-1, 7 wt % of compound I-2, 5 wt % of compound I-3 and 3 wt % of compound I-4.

[0070] The electrolyte formula comprising boron trifluoride composite lithium salt, cyclic sulfonate compounds and lithium oxalate salt proposed in the present invention is particularly suitable for high-voltage battery systems using nickel cobalt manganese oxide ternary materials as positive electrodes, especially high-voltage battery systems ≥4.3V. In other words, the electrolyte formula of the present invention can better show its advantages under the high voltage conditions of nickel cobalt manganese oxide ternary batteries. Therefore, the embodiments of the present invention prepare the electrolyte and test the corresponding performance based on the basic electrolyte formula of the ternary system.

[0071] 1. Preparation of electrolyte

[0072] Preparation of basic electrolyte 1: In a glove box filled with argon (water content <5 ppm, oxygen content <10 ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a mass ratio of 3:5:2 to form an organic solvent, and lithium hexafluorophosphate was added until the mass percentage of lithium hexafluorophosphate added based on the total mass of the electrolyte was 1 mol / L to obtain basic electrolyte 1.

[0073] According to the data in Table 1 below, add the first additive, the second additive and the third additive in a quantitative manner and mix them evenly to form an electrolyte:

[0074] Table 1 Electrolyte formula 1

[0075]

[0076]

[0077] Note: After the dosage of additives is adjusted, only the dosage of solvent in the basic electrolyte is adjusted, and the distribution ratio of each group in the solvent remains unchanged.

[0078] Vinylene carbonate (VC), the first additive, the second additive and the third additive are added to the basic electrolyte 1 according to the data in Table 2 below, and mixed evenly to form an electrolyte:

[0079] Table 2 Electrolyte formula 2

[0080]

[0081] Note: After the dosage of additives is adjusted, only the dosage of solvent in the basic electrolyte is adjusted, and the distribution ratio of each group in the solvent remains unchanged.

[0082] 0.2% by weight of vinyl carbonate (VC) and 1% by weight of vinyl sulfate (DTD) are added to the basic electrolyte 1, and the first additive, the second additive, the third additive, lithium difluorophosphate (LiDFP), lithium bis(fluorosulfonyl)imide (LiFSI), and fluoroethylene carbonate (FEC) are further quantitatively added according to the data in Table 3 below, and the mixture is uniformly mixed to form an electrolyte:

[0083] Table 3 Electrolyte formula 3

[0084]

[0085] Note: After the dosage of additives is adjusted, only the dosage of solvent in the basic electrolyte is adjusted, and the distribution ratio of each group in the solvent remains unchanged.

[0086] 2. Battery production and performance testing

[0087] The lithium-ion battery electrolytes of the above embodiments and comparative examples are respectively made into lithium-ion power batteries with a soft package capacity of 1000 mAh, wherein the lithium-ion power batteries include a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials, and the positive electrode active material is lithium nickel cobalt manganese oxide NCM712 (LiNi 0.7 Co 0.1 Mn 0.2 O2), and the negative electrode active material is graphite.

[0088] The preparation process is as follows: the positive electrode sheet, separator and negative electrode sheet are wound together into a core, sealed with an aluminum-plastic film and then baked so that the electrode moisture meets the requirements. After baking, the battery cell is injected with electrolyte, and the finished soft-pack battery cell is obtained through standing, formation, aging, capacity separation and other processes.

[0089] The prepared lithium-ion battery is tested for various properties, including:

[0090] (1) dQ / dV curve:

[0091] During the battery formation stage: charge at room temperature (25°C) at a constant current of 0.05C to 3.0V, and record the battery voltage V every 10s. n With charge capacity C n , calculate dQ as follows n / dV n value, and record the voltage V n is the horizontal axis, dQ n / dV n The value is the vertical axis, and the dQ / dV curve is drawn:

[0092] dQ n / dV n =(Q n+1 -Q n-1 ) / (V n+1 -V n-1 )*100%

[0093] Attached Figure 1 The formation dQ / dV curves of Example 1 and Comparative Examples 5, 6 and 7 are given. It can be seen from the formation dQ / dV curve of Comparative Example 6 that the first additive and the second additive are used in the electrolyte at the same time, and the ternary (NCM712) / graphite full battery film formation potential is about 2.35V~2.40V and 2.65~2.70V, which participate in the negative electrode film formation reaction and affect the SEI interface film composition.

[0094] It can be seen from the formation dQ / dV curve of Comparative Example 7 that the first additive and the third additive are used in the electrolyte at the same time, and the ternary (NCM712) / graphite full battery film formation potential is approximately 1.50V~1.60V and 2.65V~2.75V, which participate in the negative electrode film formation reaction and affect the SEI interface film composition.

[0095] It can be seen from the formation dQ / dV curve of Comparative Example 5 that the second additive and the third additive are used in the electrolyte at the same time, and the ternary (NCM712) / graphite full battery film formation potential is approximately 1.50V~1.60V and 2.30V~2.40V, which participate in the negative electrode film formation reaction and affect the SEI interface film composition.

[0096] Figure 1 The formation dQ / dV curves of the first additive, the second additive and the third additive in Example 1 of the present invention are also given. The ternary (NCM712) / graphite full battery film-forming potential has only two peaks, namely, film-forming potentials of about 1.50V to 1.60V and 2.30V to 2.40V, and the film-forming peak intensity at 2.30V to 2.40V is significantly reduced. It can be seen from this that the first additive, the second additive and the third additive have a synergistic effect when used in combination. The reason is speculated to be that the interaction of the three combined inhibits the reaction intensity of the second additive at about 2.35V to 2.40V, and inhibits the reaction consumption of non-aqueous solvents such as EC at about 2.65V to 2.75V. At the same time, the reaction amount of each additive at the negative electrode is regulated by controlling the content of the three, and the composition of the negative electrode SEI film is adjusted to form a multi-component composite SEI film.

[0097] (2) Initial impedance test:

[0098] In the battery capacity division stage: at room temperature (25°C), charge at a constant current of 0.2C to the charge cut-off voltage, and charge at a constant voltage until the current drops to 0.05C; then discharge at a constant current of 0.2C to the discharge cut-off voltage, and record the discharge capacity C1, which is the initial capacity of the battery;

[0099] Then charge at a constant current of 0.2C to the charging cut-off voltage, and charge at a constant voltage until the current drops to 0.05C; then discharge at a constant current of 0.2C until the capacity reaches 0.5*C1, i.e. 50% SOC state of charge, stand for 2 hours, and record the voltage U1;

[0100] Finally, discharge at a constant current of 4C for 30s, record the voltage U2, and calculate the initial impedance of the battery:

[0101] Initial impedance = (U1-U2) / 4*1000

[0102] (3) High temperature storage performance test

[0103] At room temperature (25°C), the battery was charged at a constant current of 1C to the charge cut-off voltage (4.4V), and then charged at a constant voltage until the current dropped to 0.05C, and then placed in a 60°C constant temperature oven for 56 days. When the battery after storage cools to room temperature, the initial volume V1 and the volume after storage V2 are recorded; the battery is discharged at a constant current of 1C to the discharge cut-off voltage, and the initial discharge capacity C2 and the discharge capacity C3 after storage are recorded; and the high-temperature storage volume expansion rate and capacity retention rate are calculated as follows:

[0104] High temperature storage volume expansion rate = (V2 / V1-1)*100%

[0105] High temperature storage capacity retention rate = C3 / C2*100%

[0106] (4) High temperature cycle performance test

[0107] At 45°C, charge at a constant current of 1C to the charge cut-off voltage, then charge at a constant voltage until the current drops to 0.05C, then discharge at a constant current of 1C to the discharge cut-off voltage. Repeat this cycle for a specific number of weeks, record the discharge capacity C4 of the first week and the discharge capacity C5 of the last week, and calculate the capacity retention rate of the battery cycle according to the following formula:

[0108] High temperature cycle capacity retention rate = C5 / C4*100%

[0109] (5) Low temperature discharge performance test

[0110] At room temperature (25°C), charge at a constant current of 1C to the charge cut-off voltage, then charge at a constant voltage until the current drops to 0.05C, then discharge at a constant current of 1C to the discharge cut-off voltage, and record the discharge capacity C6; repeat the above charging process, then discharge at a constant current of 1C to the discharge cut-off voltage at low temperature, record the discharge capacity C7, and calculate the low-temperature discharge performance of the battery according to the following formula:

[0111] Low temperature discharge rate = C7 / C6*100%

[0112] The specific test results are shown in Table 4, Table 5 and Table 6 below:

[0113] Table 4 Ni7 / / AG-2.8~4.4V electrochemical test results

[0114]

[0115]

[0116] Table 5 Ni7 / / AG-2.8~4.4V electrochemical test results

[0117]

[0118] Table 6 Ni7 / / AG-2.8~4.4V electrochemical test results

[0119]

[0120] By comparing Comparative Example 1 with Comparative Examples 2, 3, and 4, it can be seen that the use of the first additive alone can reduce the battery impedance and improve the low-temperature discharge performance; the use of the second additive alone can improve the high-temperature storage and high-temperature cycle performance, but will increase the initial impedance and deteriorate the low-temperature performance; the use of the third additive alone can reduce the impedance and improve the low-temperature discharge performance, but will deteriorate the high-temperature storage and high-temperature cycle performance.

[0121] By comparing Example 1 with Comparative Examples 5, 6 and 7, it can be seen that only when the first additive, the second additive and the third additive are used in combination can the initial impedance of the battery be reduced and the low-temperature performance, high-temperature storage performance and high-temperature cycle performance be improved at the same time. The combination of any two additives cannot achieve this effect.

[0122] Comparing Examples 1 to 10 and Comparative Examples 8, 9, 10, and 11, it can be seen that only when the first additive, the second additive, and the third additive satisfy the relationship 0.2≤b+c≤4; 0.2≤b / c≤10; 0.07≤(b+c) / a≤20, can the effect of reducing the initial impedance of the battery and improving the low-temperature discharge performance, high-temperature storage performance, and high-temperature cycle performance be achieved. If the sum of the contents of the second additive and the third additive is too small, the negative electrode film-forming effect is not significantly improved, and the high-temperature storage and high-temperature cycle performance of the battery are deteriorated; if the sum of the contents of the two is too large, the battery impedance increases and the low-temperature discharge performance is deteriorated. If the ratio of the contents of the second additive and the third additive is too small, the negative electrode film-forming effect is not significantly improved, and the high-temperature storage and high-temperature cycle performance of the battery are deteriorated; if the ratio of the contents of the second additive and the third additive is too large, the battery impedance increases and the low-temperature discharge performance is deteriorated. If the ratio of the sum of the contents of the second additive and the third additive to the first additive is too small, the negative electrode film-forming effect will not be significantly improved, and the high-temperature storage and high-temperature cycle performance of the battery will be reduced; if the ratio is too large, the battery impedance will increase and the low-temperature discharge performance will be reduced.

[0123] By comparing Examples 1, 2, 3 with Examples 4 to 10, it can be seen that by regulating the values ​​of the contents a, b, and c of the three additives, especially when the three satisfy the relationship 1≤b+c≤2.5; 0.5≤b / c≤7.5; 1≤(b+c) / a≤12.5, the battery impedance, high temperature storage and high temperature cycle performance can be further comprehensively improved.

[0124] By comparing Example 2 with Examples 11 to 21, it can be seen that compounds A1, A2, A3, compounds II-1, II-2, II-3, II-4, II-5, II-6 and compounds III-1, III-2, III-3, III-4, III-5 all have the functions of the additives they represent and can be used interchangeably.

[0125] According to Tables 4 and 5 above, by comparing Example 2 with Examples 22-24, it can be seen that the first additive, the second additive and the third additive are further used in combination with vinylene carbonate to further reduce the initial impedance and improve the high and low temperature performance of the battery.

[0126] According to Tables 4-6 above, by comparing Example 2, Examples 22-24 and Examples 25-28, it can be seen that the first additive, the second additive and the third additive are further used in combination with vinyl sulfate, vinylene carbonate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide and fluoroethylene carbonate to further reduce the initial impedance and improve the high and low temperature performance of the battery.

Claims

1. An electrolyte having both high and low temperature performance under high voltage, the electrolyte comprising: The main lithium salt, non-aqueous solvent and additives are characterized in that the additives include: The first additive comprises at least a pyrosulfate boron trifluoride composite lithium salt having a structure shown in the following formula (I-1): The second additive is selected from the cyclic sulfonate compounds represented by the following formula (IIA) and / or (IIB): Wherein, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 are independently selected from hydrogen, C1-C3 alkyl or halogen, m and n are independently selected from 1, 2 or 3, and in each repeating unit, R5, R6, R9, R 10 are selected from the same or different substituents; The third additive is a lithium oxalate salt having a structure shown in the following formula (III): In formula (III), R 11 , R 12 independently selected from C1-C3 alkyl, C1-C3 haloalkyl or halogen, R 13 is selected from a direct bond, a C1-C3 alkylene group or a halogenated C1-C3 alkylene group, M is selected from a boron atom or a phosphorus atom, and p is selected from 1 or 2; The first additive, the second additive and the third additive account for a%, b% and c% of the total mass of the electrolyte respectively, and meet the following relationship: 0.2≤b+c≤4; 0.2≤b / c≤10; 0.07≤(b+c) / a≤20.

2. The electrolyte having both high and low temperature performance under high voltage according to claim 1, characterized in that: The amounts of the first additive, the second additive and the third additive satisfy the following relationship: 1≤b+c≤2.5; 0.5≤b / c≤7.5; 1≤(b+c) / a≤12.

5.

3. The electrolyte having both high and low temperature performance under high voltage according to claim 1 or 2, characterized in that: The amounts of the first additive, the second additive and the third additive satisfy the following relationship: 0.2≤a≤3; 0.1≤b≤2.5; 0.1≤c≤2.5。 4. The electrolyte having both high and low temperature performance under high voltage according to claim 1, characterized in that: The first additive further comprises at least one of the compounds represented by the following formulae (I-2), (I-3), (I-4), (I-5), and (I-6): The first additive contains at least 80 wt % of the pyrosulfate boron trifluoride composite lithium salt having the structure represented by formula (I-1).

5. The electrolyte having both high and low temperature performance under high voltage according to claim 4, characterized in that: The first additive contains 80 to 95 wt % of the pyrosulfate boron trifluoride complex lithium salt of the structure represented by the formula (I-1), and the rest is at least one of the compounds (I-2), (I-3), (I-4), (I-5) or (I-6).

6. The electrolyte having both high and low temperature performance under high voltage according to claim 1, characterized in that: In the second additive, R1, R2, R3, R4, R5, R6, R7, R8, R9, R 10 are independently selected from hydrogen, methyl, ethyl or halogen, m and n are independently selected from 1 or 2, and in each repeating unit, R5, R6, R9, R 10 are selected from the same or different substituents.

7. The electrolyte having both high and low temperature performance under high voltage according to claim 6, characterized in that: The second additive is selected from at least one of the cyclic sulfonate compounds shown in the following structures:

8. The electrolyte having both high and low temperature performance under high voltage according to claim 1, characterized in that: The third additive is selected from at least one of the lithium oxalate salts shown in the following structures:

9. The electrolyte having both high and low temperature performance under high voltage according to any one of claims 1 to 8, characterized in that: The additives also include a fourth additive, which is vinylene carbonate, and its mass percentage in the electrolyte is 0.1-5wt%.

10. The electrolyte having both high and low temperature performance under high voltage according to claim 9, characterized in that: The additive further comprises a basic additive, wherein the basic additive is selected from at least one of a sulfate compound, a fluorinated carbonate compound or a fluorinated lithium salt compound, and the amount thereof accounts for 0.1 to 5.0 wt% of the total mass of the electrolyte; The sulfate compound is selected from at least one of vinyl sulfate, pentaerythritol bicyclic sulfate, 4,4'-disulfate or 4-methyl-vinyl sulfate; The fluorinated carbonate compound is selected from at least one of fluoroethylene carbonate, difluoroethylene carbonate, and trifluoromethylpropylene carbonate; The fluorine-containing lithium salt compound is selected from at least one of lithium difluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium difluorobis(oxalate) phosphate, lithium difluorooxalate borate, lithium trioxalate phosphate or the lithium salt represented by the following formula (IV), and the fluorine-containing lithium salt compound is different from the main lithium salt: In formula (IV), y+z=4, y≥0 and z≥1, and y and z are positive integers.

11. The electrolyte having both high and low temperature performance under high voltage according to claim 1, characterized in that: The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluorooxalate phosphate, lithium trioxalate phosphate or lithium difluorobis(oxalatophosphate), and its molar concentration is 0.1-4.0 mol / L; The non-aqueous solvent is selected from at least one of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, fluoroethylene carbonate, difluoroethylene carbonate, γ-butyrolactone, methyl acetate, methyl propionate, methyl butyrate, ethyl acetate, ethyl propionate, ethyl butyrate, propyl acetate, propyl propionate, cyclopentane, dimethyl sulfoxide, dimethyl sulfone, diethyl sulfone, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether or 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

12. A lithium ion secondary battery comprising a positive electrode, a separator and a negative electrode, characterized in that: The lithium-ion secondary battery is also filled with the electrolyte described in any one of claims 1-11.

13. The lithium ion secondary battery according to claim 12, characterized in that: The active material of the positive electrode includes: ternary nickel cobalt lithium manganese oxide, lithium cobalt oxide, lithium manganese iron phosphate, spinel lithium manganese oxide or nickel manganese oxide, and the active material of the negative electrode is selected from graphite and / or silicon negative electrode materials.

14. The lithium-ion secondary battery according to claim 13, characterized in that: The ternary nickel-cobalt-manganese-oxide lithium is selected from NCM523, NCM622, NCM712, NCM811 or NCM90505.

15. The lithium ion secondary battery according to claim 14, characterized in that: The cut-off voltage of the lithium-ion secondary battery is ≥4.3V.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte solution

    CN103943884A

  • High-energy-density battery electrolyte

    CN118173885A

  • Application of pyrosulfate boron trifluoride composite lithium salt in electrolyte

    CN118173890A

  • Battery electrolyte additive and electrolyte giving consideration to high and low temperature properties as well as nickelic ternary lithium ion battery

    CN109755635A

  • Lithium-ion battery electrolyte and lithium-ion battery containing same

    CN111029653A

Cited By

  • Acetonitrile-based electrolyte compatible with high and low temperature performance and preparation method thereof

    CN122576376A